A review of cathode and anode materials for lithium-ion batteries - Mekonnen, Yemeserach; Sundararajan, Aditya; Sarwat, Arif I. (Proceedings of IEEE Southeastcon, 2016)
Lithium ion batteries are one of the most commercially sought after energy storages today. Their application widely spans from Electric Vehicle (EV) to portable devices. Their lightness and high energy density makes them commercially viable. More research is being conducted to better select the materials for the anode and cathode parts of Lithium (Li) ion cell. This paper presents a comprehensive review of the existing and potential developments in the materials used for the making of the best cathodes, anodes and electrolytes for the Li-ion batteries such that maximum efficiency can be tapped. Observed challenges in selecting the right set of materials is also described in detail. This paper also provides a brief history of battery technology and their wide applicability in the energy market today, the chemistry and principle of operation behind the batteries, and their potential applications even beyond the energy sector. Safety concerns related to Li-ion batteries have also been taken into account considering recent events.